Nepalese Esthetic Dental (NED) Proportion in Nepalese Population - Rokaya, D.; Kitisubkanchana, J.; Wonglamsam, A.; Santiwong, P.; Srithavaj, T.; Humagain, M. (Kathmandu University Medical Journal, 2017)
Background Lots of studies on maxillary anterior teeth proportions have been studied in different populations in various countries, but no studies have been conducted in Nepal on the esthetic maxillary anterior teeth proportions. Objective The study was done to investigate the maxillary anterior teeth proportions in a Nepalese population. Teeth proportions in the total population were compared with golden proportion (GP) and golden standard (GS). Method A total of 150 Nepalese subjects were divided in three facial types; broad, average and narrow group. Maxillary anterior teeth were measured from dental casts using digital calipers. The perceived width ratios of lateral to central incisor (LI/CI) and canine to lateral incisor (CN/LI), ratios of mean central incisor length to 2 central incisor widths (CIL/2CIW), and actual width to length ratios (WLRs) (%) were calculated in each facial type and compared. Mean LI/CI, CN/LI and CIL/2CIW in total population were calculated and compared with GP (0.618), and mean WLRs in the total population were compared with GS (80%). All teeth proportions were compared among three facial types. One-sample t-test and one-way ANOVA were performed to analyze the data (α = 0.05). Result The LI/CI, CN/LI, CIL/2CIW and WLRs in three facial types showed no significant difference. The LI/CI, CN/LI and CIL/2CIW in the total population were 66%, 70% and 55% respectively, and were significantly different from GP. The WLRs for CI, LI and CN in the total population were 90%, 86% and 89% respectively and significantly differed from GS. These values were considered to constitute the Nepalese Esthetic Dental (NED) proportion. Conclusion No significant difference of maxillary anterior teeth proportions were observed among three facial types. Teeth proportions in the total population significantly differed from GP and GS. We propose the NED proportion as a guideline for dental treatment in the maxillary anterior region in Nepalese populations.